2018
DOI: 10.1136/ebmental-2018-300037
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in youth with autism spectrum disorders: systematic review and meta-analysis of subjective and objective studies

Abstract: BackgroundSleep problems are common and impairing in individuals with autism spectrum disorders (ASD). Evidence synthesis including both subjective (ie, measured with questionnaires) and objective (ie, quantified with neurophysiological tools) sleep alterations in youth with ASD is currently lacking.ObjectiveWe conducted a systematic review and meta-analysis of subjective and objective studies sleep studies in youth with ASD.MethodsWe searched the following electronic databases with no language, date or type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
75
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 59 publications
(19 reference statements)
12
75
2
Order By: Relevance
“…Conditions that co‐occur with ASD have diverse pathophysiological characteristics. Studies have found gastrointestinal (GI) symptoms [Holingue, Newill, Lee, Pasricha, & Daniele Fallin, ], sleep disorders [Díaz‐Román, Zhang, Delorme, Beggiato, & Cortese, ], immune‐mediated disorders [Hughes, Mills Ko, Rose, & Ashwood, ], epilepsy [Woolfenden, Sarkozy, Ridley, Coory, & Williams, ], and many other conditions [Kohane et al, ; Mannion, Leader, & Healy, ; Muskens, Velders, & Staal, ; Rydzewska et al, ] to affect substantial numbers of individuals with ASD. Although seemingly distinct, some studies have suggested that certain COCs tend to co‐occur together [Aldinger, Lane, Veenstra‐VanderWeele, & Levitt, ; Fulceri et al, ; Hirata et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Conditions that co‐occur with ASD have diverse pathophysiological characteristics. Studies have found gastrointestinal (GI) symptoms [Holingue, Newill, Lee, Pasricha, & Daniele Fallin, ], sleep disorders [Díaz‐Román, Zhang, Delorme, Beggiato, & Cortese, ], immune‐mediated disorders [Hughes, Mills Ko, Rose, & Ashwood, ], epilepsy [Woolfenden, Sarkozy, Ridley, Coory, & Williams, ], and many other conditions [Kohane et al, ; Mannion, Leader, & Healy, ; Muskens, Velders, & Staal, ; Rydzewska et al, ] to affect substantial numbers of individuals with ASD. Although seemingly distinct, some studies have suggested that certain COCs tend to co‐occur together [Aldinger, Lane, Veenstra‐VanderWeele, & Levitt, ; Fulceri et al, ; Hirata et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…ASD is a pervasive neurodevelopmental disorder, with prevalence between 1/34 and 1/76 (Baio et al, ). Sleep disorders are claimed to be present in up to 80% of ASD children, most often characterized by longer sleep onset latency and reduced sleep efficiency (Diaz‐Roman, Shang, Delorme, Zhang, Delorme, Beggiato, & Cortese, ; Fletcher et al, ; Souders et al, ). However, few studies have utilized polysomnography to objectively explore sleep in children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we evaluated the full-texts of 86 articles and excluded 60 articles that did not meet all the criteria of this review. Finally, 26 articles meeting all the criteria were included in this umbrella review (see Table 3), including 14 systematic reviews (Arnevik and Helverschou, 2016;Hannon and Taylor, 2013;Hedley and Uljarević, 2018;Kalyva et al, 2016;Menezes et al, 2018;Nickel et al, 2019;Padgett et al, 2010;Richa et al, 2014;Segers and Rawana, 2014;Skokauskas and Gallagher, 2009;Stewart et al, 2006;Vannucchi et al, 2014;Wigham et al, 2017;Zahid and Upthegrove, 2017) and 12 meta-analyses (De Giorgi et al, 2019;Díaz-Román et al, 2018;Elrod and Hood, 2015;Hollocks et al, 2019;Hudson et al, 2019;Lai et al, 2019;Lugo-Marín et al, 2019;Lugo Marín et al, 2018;Morgan et al, 2020;van Steensel et al, 2011;van Steensel and Heeman, 2017;Zheng et al, 2018).…”
Section: Resultsmentioning
confidence: 99%